Variation in the Abundance of OsHAK1 Transcript Underlies the Differential Salinity Tolerance of an indica and a japonica Rice Cultivar - Chen, Guang; Liu, Chaolei; Gao, Zhenyu; Zhang, Yu; Zhang, Anpeng; Zhu, Li; Hu, Jiang; Ren, Deyong; Yu, Ling; Xu, Guohua; Qian, Qian (Frontiers in Plant Science, 2018)
Salinity imposes a major constraint over the productivity of rice. A set of chromosome segment substitution lines (CSSLs), derived from a cross between the japonica type cultivar (cv.) Nipponbare (salinity sensitive) and the indica type cv. 9311 (moderately tolerant), was scored using a hydroponics system for their salinity tolerance at the seedling stage. Two of the CSSLs, which share a ~1.2 Mbp stretch of chromosome 4 derived from cv. Nipponbare, were as sensitive to the stress as cv. Nipponbare itself. Fine mapping based on an F2 population bred from a backcross between one of these CSSLs and cv. 9311 narrowed this region to 95 Kbp, within which only one gene (OsHAK1) exhibited a differential (lower) transcript abundance in cv. Nipponbare and the two CSSLs compared to in cv. 9311. The gene was up-regulated by exposure to salinity stress both in the root and the shoot, while a knockout mutant proved to be more salinity sensitive than its wild type with respect to its growth at both the vegetative and reproductive stages. Seedlings over-expressing OsHAK1 were more tolerant than wild type, displaying a superior photosynthetic rate, a higher leaf chlorophyll content, an enhanced accumulation of proline and a reduced level of lipid peroxidation. At the transcriptome level, the over-expression of OsHAK1 stimulated a number of stress-responsive genes as well as four genes known to be involved in Na+ homeostasis and the salinity response (OsHKT1;5, OsSOS1, OsLti6a and OsLti6b). When the stress was applied at booting through to maturity, the OsHAK1 over-expressors out-yielded wild type by 25%, and no negative pleiotropic effects were expressed in plants gown under non-saline conditions. The level of expression of OsHAK1 was correlated with Na+/K+ homeostasis, which implies that the gene should be explored a target for molecular approaches to the improvement of salinity tolerance in rice.